Ensuring Quality Safety in Schools: A Participatory Action Research Approach - Mabade, Avhurengwi Samson (Advances in Social Sciences Research Journal, 2021)
The focus of this article is on the quality safety in Schools. Although safety in schools is a worldwide problem, in South Africa this seems to be getting worse for they are broken into, vandalized and set alight in vast majority. Taking a heed to around 1600 number of schools robbed, vandalized and torched during this frustrating and terrifying period of COVID -19, one would agree that schools are not protected. People seemed to have lost ethics and ownership towards schools. Schools appeared to be the safest place as well as conducive for study in the previous decades. Safety school promotes social and creative learning. Schools are robbed their groceries, equipments including computers and other paraphernalia for learning and teaching support. On the 10th July 2020, four schools in Limpopo Province had been broken into and all groceries were robbed at a gun point. Taking a number of instances into consideration, which occurred before horrifying situation of Covid-19, one would see a need for an investigation. Although schools are advised to establish tight and quality security fence, school equipments and groceries are still not safe. There is a variety of literature which focused on the roles of teachers, administrators and students in creating safe schools. For this study, the researcher focused on the role of Community towards ensuring quality safety in school as a Community resource. Therefore it is the Community’s obligation to ensure quality safety in Schools. Community needs to develop strategies to ensure safety in Schools for their children. In this study, the researcher established a model which is Community Support Team versus School Support Team. Therefore the researcher adopted a Participatory Action Research Approach to empower Community to strategize for ensuring quality safety in Schools. The researcher employed qualitative technique to collect data from the community members around four selected schools in a rural area.